Flavonoid dalam Food Bar Berbasis Jantung Pisang sebagai Sumber Laktagogue - Yaktiworo Indriani; Sofyan Musyabiq Wijaya; Wiwi Febriani; Andi Eka Yunianto; Ramadhana Komala (Universitas Airlangga, 2026)
Background: Banana blossoms are widely available in tropical countries such as Indonesia, but are rarely used to their full potential. Flavonoids are bioactive compounds that act as lactagogues and can help stimulate breast milk production. Objectives: This study aimed to analyze the flavonoid content in banana blossom-based food bars as a potential lactagogue source. Methods: This study used a Completely Randomized Design (CRD) with 4 treatments varying the amount of banana blossom flour: F1=0 g, F2=10 g, F3=15 g, and F4=20 g. Every formulation was used with a 2g sample to determine flavonoid content. The flavonoid content was analyzed using UV-Visible spectrophotometry at a maximum wavelength of 413 nm. Data analysis using SPSS version 22 and Duncan's Multiple Range Test (DMRT) was used to test differences in flavonoid content among banana flower food bar formulations. Results: The results showed a statistically significant difference (p-value<0.05) among the various formulations. Formulation F3 had a higher flavonoid content compared to the other formulas, at 1.19 mg. Conclusions: The F3 formulation exhibited the highest flavonoid content and has potential as a nutritious snack food that functions as a lactagogue. These findings indicate that the use of banana blossoms in the form of food bars can be a practical, functional food alternative to help increase breast milk production in breastfeeding mothers.